2017
DOI: 10.24838/ip.2017.v70.i3.72488
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Yield Loss of Mustard Due to Alternaria Leaf Blight in Gangetic Plains of West Bengal

Abstract: Alternaria leaf blight of mustard caused by Alternaria brassicae and Alternaria brassicicola occur severely in different districts of West Bengal. A mustard variety 'Binoy' was used to assess the effect of iprodion. Three sprays of iprodion @0.2% at 10 days interval beginning from 45 days after sowing resulted in lowest Alternaria blight under moderate disease pressure and four sprays for high disease pressure resulted in highest seed yield and cost benefit ratio of 5.19 and 4.61, respectively for commercial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…The result of the experiment clearly indicates that five numbers of fungicidal sprays on the susceptible variety like Sonali, reduce the disease levels significantly. These findings are in agreement with those of Mahapatra and Das (2017), who reported the reduction in AUDPC values of Alternaria leaf blight in mustard with increased number of Iprodione sprays. Shukla et al (2014) suggested that two sprays of Carbendazim (0.1%) were sufficient to manage the disease severity.…”
Section: Assessment Of Effect Of Anthracnose Disease On Yield Of Greesupporting
confidence: 93%
“…The result of the experiment clearly indicates that five numbers of fungicidal sprays on the susceptible variety like Sonali, reduce the disease levels significantly. These findings are in agreement with those of Mahapatra and Das (2017), who reported the reduction in AUDPC values of Alternaria leaf blight in mustard with increased number of Iprodione sprays. Shukla et al (2014) suggested that two sprays of Carbendazim (0.1%) were sufficient to manage the disease severity.…”
Section: Assessment Of Effect Of Anthracnose Disease On Yield Of Greesupporting
confidence: 93%
“…Sacc. and Alternaria brassicicola is one among the important diseases of Indian Mustard with severe losses up to 70% in Rapeseed (Brassica campestris) (Kolte 2002); (Kolte et al, 1987), which had reported from across the globe causing 10-70% yield losses in which 15 to 71% losses were reported from India (Kadian and Saharan, 1983;Ram and Chauhan, 1998) depending on the crop species, being high in Brassica rapa with 35-40% in Indian Mustard (Chattopadhyay, 2008). These fungal pathogens chase the crops in every stage of the crop growth ultimately resulting in huge losses in the quality of the produce.…”
Section: Introductionmentioning
confidence: 99%
“…(Sinha et al, 1992;Meena et al, 2011;Biswas, 2013;Kumar et al, 2013). The role of environmental factors in disease development as well as suitable chemical measures for disease control have been previously studied by many workers (Jagana et al, 2013;Kumar et al, 2014;Mahapatra and Das, 2016;Mahapatra et al, 2018).…”
Section: Introductionmentioning
confidence: 99%